2015
DOI: 10.2151/jmsj.2015-048
|View full text |Cite
|
Sign up to set email alerts
|

Clouds and the Earth’s Radiant Energy System (CERES) Data Products for Climate Research

Abstract: NASA's Clouds and the Earth's Radiant Energy System (CERES) project integrates CERES, Moderate Resolution Imaging Spectroradiometer (MODIS), and geostationary satellite observations to provide top-of-atmosphere (TOA) irradiances derived from broadband radiance observations by CERES instruments. It also uses snow cover and sea ice extent retrieved from microwave instruments as well as thermodynamic variables from reanalysis. In addition, these variables are used for surface and atmospheric irradiance computatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…We are able to compare satellite data products such as DARDAR directly with the GSRM output in a statistical sense. Unfortunately, satellite sampling of microphysical properties is difficult and local radiative fluxes (and heating) can only be determined by model construction using satellite constraints (see, e.g., KATO et al., 2015). In situ aircraft measurements taken when satellite data is also available can provide meaningful comparisons of model microphysics and radiation simultaneously, but such aircraft measurements are limited (see Bucci et al., 2020, for a recent effort to make such measurements).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…We are able to compare satellite data products such as DARDAR directly with the GSRM output in a statistical sense. Unfortunately, satellite sampling of microphysical properties is difficult and local radiative fluxes (and heating) can only be determined by model construction using satellite constraints (see, e.g., KATO et al., 2015). In situ aircraft measurements taken when satellite data is also available can provide meaningful comparisons of model microphysics and radiation simultaneously, but such aircraft measurements are limited (see Bucci et al., 2020, for a recent effort to make such measurements).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The CERES project as a successor to Earth Radiation Budget Experiment (ERBE) has been providing radiative flux components from 2000 to till date [6,43,122]. CERES program focused on measuring outgoing longwave radiation (OLR) radiances and reflected solar radiances to an accuracy of 1% and 2%, respectively.…”
Section: Ceres/modis (Cm)mentioning
confidence: 99%
“…The ERBE [5,6] program provided significant information about the energetics and the effects of clouds in modulating the energy balance [31,82]. The CERES project conceived as a successor to ERBE to compile a data record for the investigation of interannual variations of climate [31,43,122]. In the present study, we have used daily averaged CM observed Geostationary enhanced, temporally interpolated surface radiative fluxes for all-sky conditions (version 3) data of Q S and Q L .…”
Section: Ceres/modis (Cm)mentioning
confidence: 99%
“…Used are the global surface flux data for total sky condition of Clouds with the Earth's Radiant Energy System SYN1deg‐day which are described as “The Synoptic Radiative Fluxes and Clouds (SYN1deg‐Day)” products that contain a day of space and time averaged Clouds with the Earth's Radiant Energy System geostationary enhanced temporally interpolated data (Kato et al, ). The 1° regional fluxes are daily averages from the Synoptic Radiative Fluxes and Clouds (SYN1deg‐1Hour) product.…”
Section: Datamentioning
confidence: 99%